Combination therapy (ultrasound and electrotherapy) in the reduction of abdominal adiposity: case reports - Costa, Raíssa Biff (2017)
Introduction: The accumulation of fat in the abdomen region, besides being related to cardiovascular health and metabolic problems, has become a relevant aesthetic issue because it influences the psychosocial health of individuals. Objective: To evaluate the effects of Combined Therapy, through ultrasound and electrotherapy, on abdominal adiposity of women. Methods: This is a case study in which 9 women (30.33 ± 8.5 years) underwent 10 therapy sessions, 2 times / week, for 5 weeks. The evaluation of the treated area was performed through perimetry, plicometry and total body densitometry examinations before and after intervention. Results: The results of densitometry showed that the combination of ultrasound and electrotherapy reduced the abdominal fat percentage by 2.44 ± 2.31. Perimetry and plicometry showed reductions in waist circumference and supra-iliac and abdominal skinfolds. Conclusion: In this case study, intervention through combination therapy proved to be effective in reducing abdominal adiposity in women.